Study of the internal structure of long GRBs with similar redshift - Quirola, Jonathan; Vasquez, Nicolás (TECCIENCIA, 2016)
In this paper, we studied the internal structure, temporal and spectral, of a sample of 5 long GRBs detected by Swift satellite with similar redshift (z~1). We determined the spectral lag applying an exponential model, proposed by Norris, according to the sensitivity of the BAT detector (15-150 KeV); on the other hand, we analyzed the spectrum in regions of 1 second width, and the temporal evolution of spectral parameters such as photon index and energy peak, and finally we investigated correlations between spectral lag and photon index or luminosity. For the spectral analysis we used three spectral models: power law, cut-off power law and band model. We concluded that high energy photons arrived before low energy photons in 88% of lags, the contribution of the synchrotron radiation inside the burst is important for the 66.67% of analyzed regions. Moreover, the spectral lag and luminosity are anticorrelated, nevertheless spectral lag and photon index are not correlated.